Пикник на обочине: [фантастический роман] / Аркадий Стругацкий, Борис Стругацкий - Стругацкий Аркадий Натанович (АСТ, 2015)
Экземпляры: ф.4 (20160712) / Инвентарный номер: 2683 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 87 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445